Natural history of relapsed myeloma, refractory to immunomodulatory drugs and proteasome inhibitors: a multicenter IMWG study - Kumar, Shaji; Goldschmidt, Hartmut; Hillengaß, Jens (Leukemia, 2017)
Introduction of new myeloma therapies offers new options for patients refractory to immunomodulatory drugs (IMiDs) and proteasome inhibitors (PIs). In this multicenter study, patients with relapsed multiple myeloma, who have received at least three prior lines of therapy, are refractory to both an IMiD (lenalidomide or pomalidomide) and a PI (bortezomib or carfilzomib), and have been exposed to an alkylating agent were identified. The time patients met the above criteria was defined as time zero (T0). Five hundred and forty-three patients diagnosed between 2006 and 2014 were enrolled in this study. Median age at T0 was 62 years (range 31-87); 61% were males. The median duration between diagnosis and T0 was 3.1 years. The median number of lines of therapy before T0 was 4 (range 3-13). The median overall survival (OS) from T0 for the entire cohort was 13 (95% confidence interval (CI) 11, 15) months. At least one regimen recorded after T0 in 462 (85%) patients, with a median (95% CI) progression-free survival and OS from T0 of 5 (4, 6), and 15.2 (13, 17) months, respectively. The study provides the expected outcome of relapsed multiple myeloma that is refractory to a PI and an IMiD, a benchmark for comparison of new therapies being evaluated.